Life skills activities for special children - Mannix, Darlene (West Nyack, N.Y. : Center for Applied Research in Education, 1992)
Basic survival skills. Personal independence. Community independence. Getting along with others.
Keywords: Education; Mentally handicapped children -- United States -- Life skills guides; Life skills -- Study and teaching (Primary) -- United States